PSYCHOSOCIAL FACTORS ASSOCIATED WITH MENTAL HEALTH ISSUES AMONG ADOLESCENTS: LITERATURE REVIEW - Harahap, Ade Ramadhani; Lumbantobing, Ayu Revayanti; Sinaga, Siti Nurmawan; Basri, Nuriyanti; Sari, Devi Yulika (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Adolescent mental health has become a critical global and local concern, yet it is frequently overlooked in routine community health interventions. Psychosocial development during this transition period significantly determines future productivity and quality of life. Objectives: This study aimed to review and analyze the psychosocial determinants and peer-led educational strategies associated with adolescent mental health status. Methods: This study utilized a Systematic Literature Review (SLR) design across Google Scholar, ScienceDirect, and PubMed databases, analyzing publications (2022–2026) focusing on community health education, peer counseling, and psychosocial behaviors. Out of 26 potential articles identified, 10 met the inclusion criteria and were selected for data extraction and thematic synthesis, Results: The synthesis shows that parental socioeconomic background, family support systems, and peer-to-peer interactive environments are primary drivers of adolescent psychological well-being. Peer-education frameworks demonstrate a high effectiveness level, improving self-efficacy and psychological awareness among youth by up to 3.5 times compared to generic approaches. Furthermore, structured counseling integrated within academic frameworks significantly cushions the negative impacts of social anxiety and nutritional-related stigma. Conclusions: Strengthening multi-sectoral adolescent care through peer education and family-centered psychological innovation is highly recommended to enhance mental resilience.